The AN INTELLIGENT CONTROL TECHNIQUE ANALYSIS FOR SENSORLESS PREDICTIVE CURRENT CONTROLLED DC–DC CONVERTER (International Journal of Engineering Management Science, 2022)
For a sensor less predictive current controlled boost dc–dc converter, its small-signal model that contains a number of parasitic parameters, is derived in this paper. This model indicates that the type of system becomes type 0 even with the correction of voltage loop proportional–integral controller, leading to the existence of output voltage steady-state error. Then a self-correction differential current observer (SDCO) is proposed to eliminate this steady-state error and gain high transient response speed. The self-correction part of the SDCO makes the system become type 1 to achieve no steady-state error for output voltage, whereas the differential part can guarantee that the intermediate calculation results do not overflow. By carrying out a series of simulation verifications, further investigation proves that the proposed algorithm has good robustness. A digital current-mode controller for dc-dc converters is introduced. The current control mode proposed current observer and PCC algorithm. It achieves the highest observation accuracy by compensating for all the known parasitic parameter. By employing the optimal current observer-based predictive current controller, a boost converter is implemented. The current-mode loop is sensor less, relying on constants and internal loop states. Fast current-mode control mechanism is implemented. This control scheme is that it facilitates the application of a low resolution PWM.